The value of survival gains from therapeutic innovations for US patients with relapsed/refractory multiple myeloma - Joanna P MacEwan; Istvan Majer; Jacquelyn W Chou; Sumeet Panjabi (Therapeutic Advances in Hematology, 2021)
Aims: This study quantifies the value of survival gains attributable to novel treatments approved since 2003 for United States (US) patients with relapsed/refractory multiple myeloma (RRMM). Methods: We estimated the increase in survival attributable to lenalidomide and bortezomib for multiple myeloma (MM) patients in the 1983–2013 Surveillance, Epidemiology, and End Results (SEER) registry. To estimate the survival benefit of treatments approved since 2015 (carfilzomib, elotuzomab, daratumumab, used in combination with lenalidomide and dexamethasone) we used clinical trial data to calibrate survival estimated using the SEER data. We then conducted an economic valuation of the estimated shift in survival curves for all therapies. Finally, we estimated the share of the value accruing to patients and manufacturers using treatment costs estimated from MarketScan data. Results: The introduction of bortezomib in combination with dexamethasone (Vd) and lenalidomide in combination with dexamethasone (Rd) resulted in substantial survival gains and societal value for multiple myeloma patients, generating 1.7 additional life-years per RRMM patient. More recently, approved novel treatments have improved survival over effective treatments (i.e. Rd/Vd) by an additional 2.5 life-years – the monetary value of this incremental survival benefit far exceeds the incremental cost of treatment. At the patient level, the incremental benefit of Rd/Vd is $335,500 and with novel treatments is $565,000. Applying this benefit to all future cohorts of US RRMM patients translates into a value of at least $75 billion and $130 billion with Rd/Vd and the novel treatments, respectively. Conclusions: SEER registry data were only available through 2013. Therefore, survival gains for recently approved treatments were estimated based on clinical trials, rather than observed survival. Our valuation analysis does not capture sources of value aside from survival gains, for example, better quality of life, increased productivity, or the value of surviving until subsequent novel therapies become available. Substantial extensions in life expectancy in RRMM since 2003 translate into real economic value gained by society.